The association of interleukin-4 haplotypes with chronic periodontitis in a Czech population - Izakovičová Hollá, Lydie; Fassmann, Antonín; Augustín, Peter; Halabala, Tomáš; Znojil, Vladimír; Vaněk, Jiří (Journal of periodontology, 2008)
BACKGROUND: Cytokine gene polymorphisms are known to influence the susceptibility and disease course of many chronic disorders. Recently, interleukin (IL)-4 gene polymorphisms were associated with aggressive periodontitis. The aim of this study was to test differences in the distribution of the IL-4 alleles, genotypes, and haplotypes between patients with chronic periodontitis (CP) and healthy controls in a Czech population. METHODS: The association study was conducted using an age- and smoking status-matched case-control design in patients with CP (n = 194) and healthy controls (n = 158) using the polymerase chain reaction-restriction fragment length polymorphism methods for the -590C/T, -33C/T, and intron 3 variable number tandem repeat (VNTR) variants of the IL-4 gene. RESULTS: No significant differences between patients and controls were found in allele and genotype frequencies of all three polymorphisms. Nevertheless, complex analysis revealed significant differences in haplotype frequencies between the groups (P = 0.005). The haplotype T(-590)/T(-33)/allele 2 VNTR (70 base pairs)(2) of the IL-4 gene was significantly more frequent in patients with CP than in controls (17.0% versus 11.0%; odds ratio = 1.85; 95% confidence interval: 1.19 to 2.87). CONCLUSION: The three polymorphisms in the IL-4 gene act in a cooperative fashion and suggest that the high-production IL-4 haplotype was associated with an increased risk for CP in the Czech population.
Keywords: tandemové repetitivní sekvence; dospělí; 5' Flanking Region; Base Pairing; Genotype; Female; cytosin; polymerázová řetězová reakce; interleukin-4; polymorfismus délky restrikčních fragmentů; Adult; Chronic Periodontitis; ženské pohlaví; Polymerase Chain Reaction; jednonukleotidový polymorfismus; introny; Cytosine; párování bází; lidé; Gene Frequency; Polymorphism, Single Nucleotide; genotyp; Introns; genetická predispozice k nemoci; studie případů a kontrol; Tandem Repeat Sequences; Genetic Predisposition to Disease; frekvence genu; Thymine; Polymorphism, Restriction Fragment Length; chronická parodontitida; Interleukin-4; Male; Case-Control Studies; Haplotypes; Exons; Czech Republic; polymorfismus genetický; alely; thymin; Česká republika; Alleles; exony; lidé středního věku; haplotypy; mužské pohlaví; 5' přiléhající oblast DNA; Polymorphism, Genetic; Middle Aged; Humans